2017
DOI: 10.1002/star.201700064
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exogenous strains on in vitro fermentation and anti‐colon cancer activities of maize resistant starch and xylo‐oligosaccharides

Abstract: The aim of this study was to assess the potential impact of 10 exogenous strains on acid production of maize resistant starch (RS) and xylo‐oligosaccharides (XOS) during in vitro fermentation and on anti‐colon cancer activities of fermentation products. Maize RS and XOS were fermented in vitro by the fecal extract from healthy adults in the absence and presence of one exogenous strain culture. Fermentation products were measured for their acetate, propionate, butyrate, and lactate contents, and growth inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A considerable amount of literature has been published on the direct relationship between RS intake and reduction of the large bowel cancer risks either in vitro or in vivo; it seems that RS may be a major protective factor against colorectal cancer (Panebianco et al 2017;Yin and Zhao 2017).…”
Section: Health Effects Of Banana Bioactive Compoundsmentioning
confidence: 99%
“…A considerable amount of literature has been published on the direct relationship between RS intake and reduction of the large bowel cancer risks either in vitro or in vivo; it seems that RS may be a major protective factor against colorectal cancer (Panebianco et al 2017;Yin and Zhao 2017).…”
Section: Health Effects Of Banana Bioactive Compoundsmentioning
confidence: 99%
“…Ot can reach the colon and be fermented by intestinal microbiota bacteria, producing short chain fatty acids and other organic acids (Fuentes-Zaragoza et al, 2010;Haenen et al, 2013). A number of studies have shown the positive effects of resistant starch in cases of obesity (Bodinham et al, 2010), cardiovascular disease (Morita et al, 2005), diabetes (Zhou et al, 2014) and colon cancer (Yin & Zhao, 2017;Panebianco et al, 2017;Cray et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the environment becomes undesirable for pathogenic microorganisms, and consequently reduces the risk of cancer cell formation (Khalili & Amini, 2015). Some studies have shown that resistant starch can prevent colorectal cancer (Panebianco et al, 2017;Yin & Zhao, 2017).…”
Section: Introductionmentioning
confidence: 99%